Comparing breast cancer imaging characteristics of CHEK2 with BRCA1 and BRCA2 gene mutation carriers. Issue 146 (January 2022) - Ghunaim, Hadeel; Laenen, Annouschka; De Keyzer, Frederik; Soens, Julie; Keupers, Machteld; Postema, Sandra; Neven, Patrick; Van Ongeval, Chantal
Abstract: Purpose: Breast cancer gene ( BRCA ) 1 and 2 mutations are frequently studied gene mutations (GM); the incidence of checkpoint kinase 2 ( CHEK2 ) is increasing. We describe the imaging features of breast cancer (BC) in CHEK2 mutations, compared to BRCA 1 and 2 using mammography, ultrasound (US) and magnetic resonance imaging (MRI). Method: Inclusion criteria were primary BC in GM carriers, treated in the same hospital. Age at diagnosis, histology, hormone receptor and human epidermal growth factor receptor 2 (HER2) status were retrieved. Mammography descriptors were mass, asymmetry and suspicious microcalcifications. The enhancement pattern (MRI), shape and border, architectural distortion, the presence of a hyperechoic rim and cystic complex structure (US) were documented. Analyses were performed using SAS software (version 9.4). Fishers' exact test was used to test associations between two categorical variables. Results: In 191 women, 233 malignant lesions were diagnosed (78 in BRCA1, 109 in BRCA2, 46 in CHEK2 ). In CHEK2 carriers, mammographically, suspicious microcalcifications (54%) were more prevalent ( BRCA2 (48%) and BRCA1 carriers (33%)) (p-value = 0.057) compared to mass lesions (35%). On US, lesions were most frequently ill-defined (86%) (p = 0.579) and irregular (94.5%) (p = 0.098) compared to BRCA2 (77% and 80% resp.) and BRCA1 carriers (71% and 72% resp.). On MRI, mass lesions showed a type 3 curve in CHEK2 (67%) compared to BRCA1 (36%) and BRCA2 (50%) (p = 0.056). Conclusions: Malignant radiological characteristics of breast cancer, more specifically suspicious microcalcifications, were more frequently seen in CHEK2 and BRCA2 compared to BRCA1 mutation carriers (without a significant difference) indicating the importance of mammography in follow-up of CHEK2 carriers.